Prevalence of chronic complications of type 2 diabetes mellitus in a secondary health centre in Niger Delta, Nigeria - Chukwuani, Ufuoma; Digban, Kester A.; Yovwin, Godwin D.; Chukwuebuni, Ngozi J. (International Journal of Research in Medical Sciences, 2016)
Background: Type 2 diabetes mellitus (T2DM) in Nigeria is believed to rapidly be on the increase despite its awareness. Its related chronic complications is also expanding leading to reduction in the quality of life of patients, incurring heavy burdens to the health care system, loss of man hours from work and increasing diabetic mortality. Current information on the prevalence of chronic complications and its related clinical characteristics in Niger Delta area is scarce. The aim of this study was to determine the prevalence of chronic complications of type 2 diabetes mellitus in a secondary health Centre in Niger Delta, with the objective of relating the effect of age and gender with these complications as well as determining their glycemic control. Methods: 200 consenting adult diabetics 96 (48%) males and 104 (52%) females, who have been attending the diabetic clinics for at least 12 months, were randomly recruited for the study. Hospital records, questionnaire and laboratory investigations were used to collect the demographic, clinical data as well as values of fasting blood sugar, urea, creatinine, lipids, urine microalbumin and glycated hemoglobin for all subjects. Results: Of the 200 T2DM patients evaluated for chronic complications, 130 (65%) presented with one form of complication varying from nephropathy (58%), dyslipidemia (57%), hypertension (48%), neuropathy (14%) and retinopathy (9%) with 104 (52%) having more than two categories concurrently. chronic complications varied with gender as well as age. Conclusions: Chronic complications are common among type 2 diabetes in central hospital Warri, Nigeria. Implementation of timely and appropriate screening strategies could decrease the burden of diabetes chronic complications.